Safety Assessment of Mli Super-insulation Systems for Cryogenic Liquid-hydrogen Tanks in Fire Scenarios - Davide Camplese; Chiara Cozzolino; Giordano Emrys Scarponi; Robert Eberwein; Frank Otremba; Valerio Cozzani (Chemical Engineering Transactions)
In the context of green energy transition, cryogenic tanks insulated by MLI and vacuum are emerging as a leading solution to store hydrogen in heavy-duty vehicles. However, the integrity of such tanks can be jeopardized by fire. In such a scenario, MLI materials degradation can occur, leaving the tank unprotected from the fire heat flux, with consequent rapid pressurization and a high risk of failure. This study presents a safety assessment of non-combustible MLI under fire exposure based on the estimation of the time to mechanical failure of the equipment. This is calculated through an innovative model that simulates the thermomechanical response of the tank, including the MLI thermal degradation and the pressure-relief valve (PRV) operation. The application to several case studies that consider a typical LH2 tank featuring a wide range of MLI configurations demonstrated the likelihood of failure in case of exposure to a hydrocarbon pool fire, providing also comprehensive insights into the impact of the insulation characteristics and operating conditions on the time to failure.